A dual-signal electrochemical immunosensor for the detection of HPV16 E6 oncoprotein based on PdBP dendritic ternary nanospheres and MBSi-Chi nanocomposites. Issue 10 (5th May 2022) - Wen, Tao; Xia, Chenchen; Yu, Qiubo; Yu, Yujie; Li, Siyuan; Zhou, Chunli; Sun, Kexin; Yue, Song
Abstract : A dual-signal electrochemical immunosensor was fabricated to detect HPV16 E6 oncoprotein for the first time, which meets the requirements for a quick and sensitive detection. Abstract : Cervical cancer is a common cancer in women. HPV16 E6 oncoprotein is a reliable biomarker for cervical cancer. Although there are other methods for detecting E6 oncoprotein, the electrochemical method has more advantages, such as low cost, convenience and speed. In this study, a novel dual-signal electrochemical immunosensor for quick and sensitive detection of E6 oncoprotein based on a high efficiency catalyst and signal label was developed. Herein, to achieve quick detection, palladium–boron–phosphorus dendritic ternary nanospheres (PdBP NSs) not only acted as a catalyst to catalyze H2 O2, but also as a support material to capture antibodies. Moreover, to realize sensitive detection, nanocomposites of mesoporous silica nanoparticles loaded with methylene blue and coated with chitosan (MBSi-Chi) were synthesized as a signal label, which can produce electrochemical signal. Under optimal conditions, the label-free immunosensor exhibited a linear range of 100 fg mL −1 to 4 ng mL −1 with a detection limit of 72.8 fg mL −1 (S/N = 3), and the sandwich-type immunosensor presented a linear range of 50 fg mL −1 to 4 ng mL −1 with a detection limit of 34.1 fg mL −1 (S/N = 3). The as-prepared dual-signal immunosensor had desirable specificity, stability and repeatability, implying its potential applications in clinical laboratory.